2013
DOI: 10.1002/ajhb.22376
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal evaluation of the relationship between first morning urinary and salivary cortisol

Abstract: Nonconjugated FMUC levels are related to non-protein-bound SC levels collected throughout the day. FMU presents several advantages over saliva for the longitudinal assessment of cortisol in naturalistic studies. Cortisol levels are about 53-fold higher in FMU than in saliva, which makes between- and within-individual variation easier to detect, and FMUC levels are less likely to be affected by confounders than diurnal SC levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 82 publications
(133 reference statements)
1
15
0
Order By: Relevance
“…Salivary cortisol levels that measure the degree of an HPA response to stress would be directly affected by cortisol binding globulin levels, which also have various confounding factors (e.g., gonadal hormones) (5). Confounding factors, such as conjugation of cortisol with carrier proteins and the time-course of cortisol clearance between samples, also need to be considered (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salivary cortisol levels that measure the degree of an HPA response to stress would be directly affected by cortisol binding globulin levels, which also have various confounding factors (e.g., gonadal hormones) (5). Confounding factors, such as conjugation of cortisol with carrier proteins and the time-course of cortisol clearance between samples, also need to be considered (7).…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive methods used to measure cortisol (i.e., saliva and urine samples) are preferable to invasive samples via venipuncture in the preterm infant population, yet usability rates for these samples range from 65% to 85% (6)(7)(8)(9)(10)(11). Saliva is the most common biological substrate used in preterm infants because it can be collected noninvasively at multiple time points, and studies have demonstrated an association between salivary cortisol and plasma levels of unbound cortisol (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FMU cortisol provides an integrative measure of basal HPAA activity and is less likely to be affected by diurnal confounders than cortisol quantified in other matrices such as serum and saliva [34,52]. Participants provided, on average, 19 ± 1.90 FMU samples each (average ± sample SD; range: 13–22).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, HPAA activity varies dramatically within individuals as a result of various confounding factors, such as circadian rhythms, food consumption and physical activity [32,33]. We have previously argued that the use of first morning urinary cortisol allows for a tighter control of these confounders than cortisol quantification in other matrices such as saliva and blood [34]. Additionally, basal HPAA activity and responsivity varies markedly within and between individuals [35,36].…”
Section: Introductionmentioning
confidence: 99%